Regulatory and Market Risk Factors and the Emissions Reduction Potential for Energy Intensive Firms - Zhengfei Guan (EDIS)
In the last decade, one of the major global environmental concerns has been greenhouse gas emissions. As part of the political debate over climate change, various policy initiatives are being proposed. Energy intensive firms that emit large amounts of greenhouse gases (e.g., floriculture or nursery firms with heated greenhouses) will be operating in an environment of high regulatory and market uncertainties in the coming years. This 3-page fact sheet presents a brief introduction of the regulatory and market risks faced by energy intensive firms and a case study of emissions reduction potential in the horticulture industry. Written by Zhengfei Guan and published by the UF Department of Food and Resource Economics, March 2013.